Mengintegrasikan Kesiapan Digital, Manajemen Sumber Daya Manusia Ramah Lingkungan, dan Inovasi Ramah Lingkungan untuk Transformasi Organisasi yang Berkelanjutan: Tinjauan Literatur Sistematis - Supriadi Siagian; Prianda Pebri; Durahman Marpaung; Jufri, Jufri; Jufrizen, Jufrizen (Jurnal Kajian dan Penelitian Umum, 2026)
Sustainable organizational transformation has become a strategic priority in the Industry 5.0 era due to increasing pressures related to Environmental, Social, and Governance (ESG) principles and the Sustainable Development Goals (SDGs). Although Digital Readiness, Green Human Resource Management (GHRM), and Eco-Innovation have been widely examined individually, studies integrating these concepts within a Sustainable Organizational Transformation (SOT) framework remain limited. This study aims to synthesize global literature and develop a conceptual model explaining the interrelationships among digital readiness, green HR practices, and ecological innovation in fostering sustainable transformation. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted. Literature was collected from Scopus, Web of Science (WoS), and ScienceDirect databases covering publications from 2020 to 2026. Of the 624 articles initially identified, 82 met the inclusion and quality assessment criteria and were analyzed using descriptive and thematic approaches. The findings reveal five major themes: Digital Readiness, GHRM, Eco-Innovation, Sustainable Organizational Transformation, and integration mechanisms among these constructs. The results indicate that Digital Readiness acts as a structural enabler that strengthens GHRM implementation and accelerates Eco-Innovation, while GHRM serves as a behavioral driver supporting sustainability-oriented transformation. This study contributes by integrating the Resource-Based View, Dynamic Capability Theory, and Natural Resource-Based View perspectives and proposes future research agendas to advance sustainability theory and organizational practice.